2019
DOI: 10.1039/c9cp05583e
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thyme essential oils using gas-phase broadband rotational spectroscopy

Abstract: A semi-quantitative analysis as well as determination of the structures and internal dynamics of components of two natural essential oils have been carried out using rotational spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Determining the abundances of the different species present, based on the intensities of rotational transitions, can be a challenging task (see ref. 60 for a complete discussion). We focused our analysis on a rather narrow frequency range (5-6 GHz) where the frequency dependence of the various components of the broadband spectrometer should be negligible.…”
Section: Intermolecular Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining the abundances of the different species present, based on the intensities of rotational transitions, can be a challenging task (see ref. 60 for a complete discussion). We focused our analysis on a rather narrow frequency range (5-6 GHz) where the frequency dependence of the various components of the broadband spectrometer should be negligible.…”
Section: Intermolecular Interactionsmentioning
confidence: 99%
“…This abundance estimation was done following the steps reported in ref. 60, and it is based on the proportionality of the relative intensities of the a-type transitions with respect to the square of the corresponding dipole-moment component in the CP-FTMW experiment. In the absence of experimental dipole moments theoretical values are used.…”
Section: Intermolecular Interactionsmentioning
confidence: 99%
“…Another technique that is aimed at studying molecules in the gas phase is broadband rotational spectroscopy. One of its main advantages is the fact that it provides unambiguous signatures of molecular components, even in complex mixtures [15,16]. Since the rotational parameters of molecular species depend on the moments of inertia, and thus on the distribution of atomic masses in the molecule, it is highly sensitive even to only small structural or mass changes.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] Several recent studies have also demonstrated the capability for rotational spectroscopy to resolve numerous mixture components without purication. 24,[28][29][30] As a result, MRR has become suitable for characterization of compounds of industrial and pharmaceutical relevance. 31 MRR identies molecules through characterization of their pure rotational transitions in the gas phase, the energies of which are governed by their molecular rotational constants.…”
mentioning
confidence: 99%
“… 23 27 Several recent studies have also demonstrated the capability for rotational spectroscopy to resolve numerous mixture components without purification. 24 , 28 30 As a result, MRR has become suitable for characterization of compounds of industrial and pharmaceutical relevance. 31 …”
mentioning
confidence: 99%